Comparative study of the physicochemical and nutritional characteristics of the grains of two varieties of sesame cultivated in two climatic zones of Burkina Faso - Oboulbiga, Edwige Bahanla; Semdé, Zénabou; Tapsoba, Fidèle Wend-Bénédo; Youl, Siébou; Nikiéma, Fulbert; Dibala, Crépin Ibingou; Hama-Ba, Fatoumata; Dicko, Mamoudou Hama (Frontiers in Food Science and Technology, 2025)
IntroductionIn Burkina Faso, sesame is one of the most widely grown oil and rend crops. Several varieties are grown in different regions, but little is known about their nutritional characteristics. The objective of this study was to evaluate the impact of the production area on the nutritional characteristics of two sesame varieties grown in Burkina Faso.MethodsThe biological material consisted of sesame varieties S42 and Humera from two production areas of Burkina Faso. The physicochemical characteristics, macronutrients, and minerals of whole and hulled grains were determined according to standard methods. The study showed a significant difference (p < 0.05) between the grain samples of the two sesame varieties from the two areas for the weight of 1,000 grains, moisture, ash, protein, fat, and carbohydrate contents, and energy values.ResultsThe color parameters (L*, a*, b*) of the samples did not show any significant difference. The mineral contents of the seeds of the two sesame varieties varied from 95.51 ± 7.07 to 1,057.01 ± 7.07 mg/100 g for Calcium, 169.32 ± 7.07 to 364.56 ± 7.07 mg/100 g for Potassium, 142.52 ± 7.14 to 261.58 ± 1.41 mg/100 g for Magnesium, 2.46 ± 7.07 to 4.54 ± 7.07 mg/100 g for Zinc, 3.48 ± 7.07 to 9.65 ± 7.07 mg/100 g for Iron with a significant difference (p < 0.05). There was a significant difference (p < 0.05) between the biochemical composition of whole and hulled sesame grains, with a decrease in ash, protein, and mineral contents and an increase in total sugars and fats.ConclusionThis study showed that the production area and hulling have an impact on the physicochemical and nutritional characteristics of the grains of sesame varieties S42 and Humera. In view of their nutritional composition, these two sesame varieties constitute a good source of nutrients. The nutritional potential of sesame will lead to increased consumption of whole or processed sesame, as well as an increase in its production in Burkina Faso.